Weight loss improves β-cell function independently of dietary carbohydrate restriction in people with type 2 diabetes: A 6-week randomized controlled trial - Thomsen, Mads N.; Skytte, Mads J.; Samkani, Amirsalar; Astrup, Arne; Fenger, Mogens; Frystyk, Jan; Hartmann, Bolette; Holst, Jens J.; Larsen, Thomas M.; Madsbad, Sten; Magkos, Faidon; Rehfeld, Jens F.; et al. (Frontiers in Nutrition, 2022)
Background: Carbohydrate restriction may benefit β-cell function and glucose metabolism in type 2 diabetes (T2D), but also leads to weight loss which in itself is beneficial. Methods: In order to determine the additional effect of carbohydrate restriction, we randomly assigned 72 adults with T2D and obesity (mean±SD HbA1c 7.4±0.7 %, BMI 33±5 kg/m2) to a carbohydrate-reduced high-protein diet (CRHP; energy percent from carbohydrate/protein/fat: 30/30/40) or an isocaloric conventional diabetes diet (CD; 50/17/33) for 6 weeks. All foods were provided free-of-charge and total energy intake was tailored individually, so both groups lost 6% of baseline body weight. Results: Despite significantly greater reductions in HbA1c (mean [95% CI] -1.9 [-3.5, -0.3] mmol/mol) after 6 weeks, during a 4-hour oral glucose tolerance test the CRHP diet neither improved glucose tolerance, β-cell response to glucose, insulin sensitivity, nor proinsulin secretion when compared to the CD diet, but increased C-peptide concentration and insulin secretion rate (area-under-the-curve [AUC] and peak) significantly more (by ~10%, P ≤ 0.03 for all). Furthermore, compared with the CD diet, the CRHP diet borderline-increased basal glucagon concentration (by 16 [-0.1, 34]%, P = 0.05), but decreased glucagon net AUC (-2.0 [-3.4, -0.6] mmol/L x 240 min, P < 0.01), decreased basal triglyceride and total AUC (by ~20%, P < 0.01 for both), and increased gastric inhibitory polypeptide total AUC (by 14%, P = 0.01). Conclusion: A moderately carbohydrate-restricted diet for 6 weeks decreased HbA1c but did not improve β-cell function or glucose tolerance beyond the effects of weight loss when compared with a conventional diabetes diet in people with T2D.